Developing Ecotourism Community Based Approach: A Sustainable Tourism Development Project on Tanjung Surat Island - Hazran, Mohd Fakharur Razziy; Shari, Mohamad Azrul; Abdul Majid, Norfazlinda; Mat Jusoh, Ami Fariza; Mohd Salleh, Kahirol (Journal of Technical Education and Training, 2024)
The Tanjung Surat Island Ecotourism Development Master Plan study was commissioned to support the Johor Southeast Development Authority (KEJORA) in creating a high-impact strategy to develop Tanjung Surat Island into a premier ecotourism destination for both local and international tourists. This study addresses the prevalent community misunderstanding regarding ecotourism development. The main objective of this study is to identify strategic planning through community engagement initiatives spearheaded by KEJORA on Tanjung Surat Island. Quantitative methods, including the distribution of questionnaires to 118 respondents, were employed to meet this objective. In addition to the questionnaires, the study incorporated several other data collection methods to ensure a thorough understanding of the community’s perspective. These included structured interviews with key stakeholders, focus group discussions with community leaders, and participatory observation to gather qualitative insights that complemented the quantitative data. The study’s findings will provide a comprehensive guide and reference for planning across economic, social, and environmental dimensions, aiding in the development of Tanjung Surat Island’s ecotourism sector. This guide will benefit KEJORA and other stakeholders, including the private sector, interested in supporting and shaping the island’s ecotourism future. Additionally, the study highlights the critical need for Technical and Vocational Education and Training (TVET) to enhance the quality of existing services, ensuring they meet current and future demands and standards.